Associations between seizure management and sleep disorders in children with epilepsy: A cross-sectional study in Medan, Indonesia - Suistaya, Novi A.; Dimyati, Yazid; Siregar, Olga R.; Harahap, Juliandi; Dewi, Ika C.; Lubis, Mahrani; Mukhtar, Fatima AS.; Alharbi, Olayan (Narra X, 2025)
Sleep disorders are prevalent in children, particularly those with chronic illnesses such as epilepsy, where they disrupt sleep quantity, quality, or timing. The aim of this study was to analyze factors associated with sleep disorder among epileptic children admitted to Haji Adam Malik General Hospital, Medan, Indonesia. The study employed cross sectional design, recruiting 49 children (4–10 years old) with epilepsy at Haji Adam Malik General Hospital from February to June 2024. Data collection was carried out using the Children's Sleep Habit Questionnaire (CSHQ) questionnaire. Further, data on Anti-Epileptic Drugs (AED) intake and history and type of seizures were collected. Pearson’s Chi-square test was employed to analyze the association of the demographic, seizure characteristics, and AED with sleeping disorder. The findings suggest that sleep disorder in children with epilepsy was prevalent (n=26, 53.1%), mostly occurring in boys (32.7%) and those receiving valproic acid (n=9, 34.6%) and its combination with levetiracetam (n=8, 30.8%). Chi-square test results showed that seizure history intake (p<0.001), AEDs intake (p<0.001), and type of AED (p=0.010) were significantly associated with sleep disorder. In conclusion, seizure management strategies and AED regimens can influence sleep disorders in children with epilepsy. Therefore, revisiting and modifying AED treatments may be required to improve both seizure control and sleep quality in affected patients.